Influence of graphene oxide on thermal, electrical, and morphological properties of new achiral polyimide. Issue 5 (3rd May 2017) - Balaji, Sadhasivam; Balasubramanian, Rukmanikrishnan; Rigana M., Fathima; Sarojadevi, Muthusamy
Abstract : In this study, a new diamine N‐[2‐(1H‐indol‐3‐yl)ethyl]‐3, 5‐diaminobenzamide (IEDAB) was synthesized using tryptamine as starting material and characterized by FT‐IR, 1 H‐NMR, 13 C‐NMR, and mass spectroscopy. Then, it was polymerized with 3, 3', 4, 4'‐benzophenone tetracarboxylic dianhydride (BTDA) via thermal imidization to produce polyimide (PI). A series PI/GO nanocomposite films were prepared by incorporating different ratios (1, 3, and 5 wt%) of synthesized GO by solution casting method. The synthesized PI was confirmed by Ubbelohde viscometer and FT‐IR spectroscopy. SEM and Raman spectroscopy showed that GO was well dispersed in the PI matrix. XRD patterns indicated the PI and PI/GO nanocomposite films were highly amorphous in nature. The synthesized PI and their nanocomposites show high thermal stability as their T 10% weight loss are in the range of 498 to 563°C with 30.6 to 40% of char yield and the glass transition temperatures ( T g s) are in the range of 188 to 262°C. The limited oxygen index (LOI) values increased from 31.4% to 56.0% with increases of 5% GO content in the PI/GO nanocomposite. They have high dielectric constant in the range of 2.6 to 5.1 at 1 MHz and also good mechanical properties with tensile strength of 81 to 116 MPa, elongation at break 5 to 9%. POLYM. ENG. SCI., 2017. © 2017 Society of Plastics Engineers